Proposta de bebida probiótica a base de água de coco - GUIMARÃES, Adalgisa Gabriela dos Santos (2023)
Functional foods can generate metabolic and or physiological beneficial effects to their consumers, in this context, probiotics are highly requested for their role as health promoters, being fermented foods the main sources, such as fermented milks and yogurt. The acidlactic bacteria are the most commonly used microorganisms in the development of probiotic foods, due their proven functional characteristics and their generally recognized as safe ingestion. As an alternative to consumption of individuals who for some reason do not eat dairy products, this study aimed to propose a formulation of a beverage with probiotic characteristics based on coconut water, lactose free and fermented by Lactobacillus casei shirota. Two formulations were made: one with industrialized coconut water (F1) and the other with in nature coconut water (F2), the pH of both was adjusted. After the inoculation of 3% (v/v) of commercialized fermented beverage, which contains acidlactic bacteria, the formulations were kept to fermentation for 48 h at 36 °C. The formulations F1 and F2 were evaluate the presence of thermotolerant coliforms (45 ºC), and at intervals of 6hour during the fermentation period the physicalchemical stability (pH and total acidity) was evaluated and the determination of microbial growth profile. The coconut water used in this experiment were presented in satisfactory sanitary conditions, according to the current legislation. The F1 formulation obtained ideal cell growth in 24 hours of fermentation, with pH and acidity range practically constant. In F2, it was necessary 12 hours to obtain the expected growth (108 109 CFU/mL), and it was noticed an increase in the acidity value during the 48 hours of analysis, along with a consequent decrease in pH. The results obtained were satisfactory and showed a potential for probiotic beverage production with the coconut water substrate. Further analysis is required for the determination of lactose and for construction of a nutritional profile of the final product, as well as a more effective analysis of the shelf life and storage of the proposed product.